1990
DOI: 10.1090/s0002-9939-1990-0990415-9
|View full text |Cite
|
Sign up to set email alerts
|

A Trüdinger inequality on surfaces with conical singularities

Abstract: Abstract.In this paper, the author establishes an isoperimetric inequality on surfaces with conical singularities, and by using it, proves a Trüdinger inequality with best constant on such surfaces. The best constants of the Trüdinger inequality are also found for a class of "symmetric" singular matrices. IntroductionRecently Troyanov [1] systematically studied the surfaces with conical singularities, the singularities Picard considered. In order to prescribe Gaussian curvature on such surfaces, he proved the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 4 publications
0
10
0
Order By: Relevance
“…We remark that Proposition 3.1 was already known in the case where is substituted by any compact twodimensional Riemannian manifold, see [16,17]. An improvement of Proposition 3.1 has been obtained in [15].…”
Section: Existence Resultsmentioning
confidence: 66%
See 3 more Smart Citations
“…We remark that Proposition 3.1 was already known in the case where is substituted by any compact twodimensional Riemannian manifold, see [16,17]. An improvement of Proposition 3.1 has been obtained in [15].…”
Section: Existence Resultsmentioning
confidence: 66%
“…We will prove the asymptotic symmetry of one-point blow-up solution sequences, that is any unbounded (with respect to n) solution sequence for (16), such that n → 8 . First of all, we note that all blow-up solutions sequences are uniformly bounded in a neighbourhood of the boundary, see Theorem 2.4.…”
Section: Qualitative Properties Of Blow-up Solutionsmentioning
confidence: 99%
See 2 more Smart Citations
“…This is made explicit in the articles [19,22]; in the former it was shown that the constant β 0 is determined by a certain isoperimetric constant associated to twodimensional, piecewise smooth domains and in the latter for two-dimensional orbit folds.…”
Section: The Inequality Of Moser and Trudingermentioning
confidence: 99%